PENGARUH PARTISIPASIl ANGGARAN, BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP SENJANGAN ANGGARAN PADA BADAN RUMAH SAKIT UMUM DAERAH KABUPATEN TABANAN - Ni Ketut Ayu Astariyani; Ni Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2020)
The budgetary gap is one of the deviations of behavior that is carried out by the paralysis of the budget which is deliberately reducing or adding the value of revenue and cost in the budget design. This study aims to find out the effect of budgetary participation, organizational culture, organizational commitment and environmental uncertainty on budgetary slack in the Regional General Hospital in Tablll Regency. This research was conducted with a survey method using a questionnaire instrument. The number of samples studied was 52 respondents using the technique of determining purposive sampling using criteria. The results of hypothesis testing show that the participatory budgetary variable and environmental uncertainty affect the budgetary slack while the organizational culture and organizational commitment do not affect the budgetary slack in the Regional General Hospital in Tabanan Regency.